Universele ontwerpprincipes : 100 manieren om het gebruiksgemak te bevorderen, de waarneming te beïnvloeden, de aantrekkingskracht te vergroten, betere ontwerpbeslissingen te nemen en leerprocessen te verbeteren. - Lidwell, William, ....-; Butler, Jill, 1969-; Holden, Kritina, ....- (Amsterdam : Bis, 2006)
Universele ontwerpprincipes is the first interdisciplinary, comprehensive reference work for designers, technicians, architects and students. This standard work for designers from all disciplines combines on each double page, the description of an established design principle with illustrated examples from practice. From the '80/20 rule' to 'chunking', from the 'Baby face-factor' to 'Ockham's razorblade' from the 'waist-hip relation' to 'cognitive dissonance'. You'll learn everything there is to know about hundreds of frequently used design principles that promote easy use, influence perception, boost appeal and improve learning processes.
Keywords: Ontwerpen